Strategi Komunikasi Perpustakaan Universitas Sumatera Utara Dalam Meningkatkan Pemanfaatan Jurnal Elektronik - Muhammad Rasyad Ghazali Saraan; Humaizi Humaizi; Syafruddin Pohan (Universitas Medan Area, 2023)
This research aims to find out how the communication strategy of librarians in increasing the utilization of electronic journals. This research focuses on a qualitative case study research method involving seven informants. The data collection techniques used were in-depth interviews, observation and documentation. The findings of this study indicate that there are still shortcomings from a simple display that does not have a meaningful message to visitors, promotions are only delivered through social media, namely Instagram. The communication strategy from the librarian is to open an electronic journal search training, called literacy class. Finally, this thesis concludes that the communication strategy is applied in the programs and promotions carried out such as the information literacy class program and its promotion through the website and Instagram as well as providing service assistance to users in the information literacy reference room at the USU library. The supporting and inhibiting factors in this study are the availability of reference room facilities and infrastructure such as computers and free wifi, the existence of support and good cooperation from the rectorate and faculty, as evidenced by providing opportunities for librarians during the PKKMB period. While the inhibiting factors are the lack of availability of the number of librarian human resources in the USU library, the absence of a budget for promotion both directly and on websites and social media and the lack of calls and invitations from lecturers to access electronic journals in the USU Library and not all electronic journals provided can be accessed outside the campus network.